A major locus involved in the formation of the radial oxygen loss barrier in adventitious roots of teosinte Zea nicaraguensis is located on the short‐arm of chromosome 3. (4th January 2017) - Watanabe, Kohtaro; Takahashi, Hirokazu; Sato, Saori; Nishiuchi, Shunsaku; Omori, Fumie; Malik, Al Imran; Colmer, Timothy David; Mano, Yoshiro; Nakazono, Mikio
Abstract: A radial oxygen loss (ROL) barrier in roots of waterlogging‐tolerant plants promotes oxygen movement via aerenchyma to the root tip, and impedes soil phytotoxin entry. The molecular mechanism and genetic regulation of ROL barrier formation are largely unknown. Zea nicaraguensis, a waterlogging‐tolerant wild relative of maize ( Zea mays ssp. mays ), forms a tight ROL barrier in its roots when waterlogged. We used Z . nicaraguensis chromosome segment introgression lines (ILs) in maize (inbred line Mi29) to elucidate the chromosomal region involved in regulating root ROL barrier formation. A segment of the short‐arm of chromosome 3 of Z . nicaraguensis conferred ROL barrier formation in the genetic background of maize. This chromosome segment also decreased apoplastic solute permeability across the hypodermis/exodermis. However, the IL and maize were similar for suberin staining in the hypodermis/exodermis at 40 mm and further behind the root tip. Z . nicaraguensis contained suberin in the hypodermis/exodermis at 20 mm and lignin at the epidermis. The IL with ROL barrier, however, did not contain lignin in the epidermis. Discovery of the Z . nicaraguensis chromosomal region responsible for root ROL barrier formation has improved knowledge of this trait and is an important step towards improvement of waterlogging tolerance in maize. Abstract : Formation of a radial oxygen loss (ROL) barrier in roots of waterlogging‐tolerant plants can enhance the longitudinal diffusion of oxygen via aerenchyma to the root tip and impede the entry of soil phytotoxins. Zea nicaraguensis, a waterlogging‐tolerant wild relative of maize ( Zea mays ssp. mays ), forms a tight ROL barrier in its roots when waterlogged, whereas maize does not. Using Z . nicaraguensis chromosome segment introgression lines in maize, we identified that the short‐arm of chromosome 3 of Z . nicaraguensis endows the inducible ROL barrier root trait. Lines with this chromosomal region had restricted ROL and reduced penetration of an apoplastic solute in the basal root zones, but these functional changes were not simply related to suberin and lignin in the outer part of the roots as visualized by histochemical staining.